EFFECT OF A NOTICE TO SURRENDER ON AN INSOLVENT’S ESTATE SUBSEQUENT TO A SALE IN EXECUTION Fourie v Edkins (740/12) [2013] ZASCA 117 (19 September 2013) - Tshegofatso Kgarabjang (Obiter, 2015)
A debtor who is unable to meet his or her contractual obligations may resort to the debt-relief measures provided by the Insolvency Act 24 of 1936 and National Credit Act 34 of 2005. The Insolvency Act provides sequestration as one of the debt-relief measures because following the sequestration order the debtor may be rehabilitated. In one hand, a debtor may apply for sequestration process by way of voluntary surrender while on the other it is also possible for a creditor to sequestrate a debtor’s estate by way of compulsory sequestration. The NCA also provides debt-relief measures because it contains provisions that are aimed at the protection of consumers who are over-indebted, and further contains measures that are aimed at preventing reckless credit granting. In Ex Parte (2009 (3) SA 376 (WCC)) the applicants applied for voluntary surrender, whereas the major portion of each of the applicants’ debts arose out of “credit agreements” as intended in the NCA. The court enquired as to why the over-indebtedness of the applicants should not be more appropriately addressed instead of the voluntary surrender under the Insolvency Act. The court refused the application for voluntary surrender and held that an applicant has to make a full disclosure of his or her other assets and liabilities in terms of section 4 of the Insolvency Act, and the court must be fully informed of the applicant’s proprietary situation. The decision in Ex Parte Ford indicates that an applicant, who brings an application for voluntary surrender instead of using remedies under the NCA such as over-indebtedness, will have to explain to the court as to why he has not resorted to the debt-relief measures provided by the NCA. According to the Insolvency Act the main aim of the sequestration process is to provide for a collective debt-collecting process that will ensure an orderly and fair distribution of the debtor’s assets in the circumstances where these assets are insufficient to satisfy all the creditors’ claims. Therefore the rights of creditors as a group will be preferred over the rights of a single creditor (concursus creditorum). The former comes into operation after a sequestration order has been granted by a court. The effect of sequestration is that the insolvent will be divested of his estate and vest in the Master at least until a trustee has been appointed. More pertinently, section 20(1)(c) of the Insolvency Act provides that one of the effects of sequestration of the estate of an insolvent is that, as soon as any sheriff or messenger, whose duty is to execute judgment given against the insolvent, becomes aware of the sequestration should stay that execution, unless the court directs otherwise. In the matter between Fourie v Edkins the Supreme Court of Appeal had to consider circumstances in which a court could exercise its discretion in terms of section 20(1)(c) of the Insolvency Act, to stay the execution in the instance where a sheriff had sold immovable property in the execution of judgment, pursuant to a sale agreement concluded before the insolvent applied for sequestration of his or her estate and also prior to the registration of the transfer of the property in the name of the execution purchaser. The aim of this note is to analyse the decision in Fourie v Edkins in light of section 20(1)(c) of the Insolvency Act which deals with the effects of sequestration. Brief reference will also be made to other cases relating to section 20(1).